Peranan Gereja Mengatasi Kekerasan yang Dialami Remaja dalam Keluarga - Harefa, Mangali (Sekolah Tinggi Teologi IKAT Jakarta, 2020)
Violence is often experienced by adolescents, both in physical form where adolescents experience abusive treatment or in the form of verbal and psychological violence, where adolescents are often scolded with swear words and insults. Psychological violence experienced by adolescents is often threatened, always regulated and ordered by perpetrators. In addition, adolescents also experience violence in the form of financial violence, where adolescents get restrictions and controls on financial matters that are not appropriate. Crisis counseling is one way to deal with family violence experienced by adolescents. The crisis intervention method is a method to help individuals cope with negative and destructive emotional responses due to events that cause a crisis. One implementation of the crisis intervention method is the ABC method; (A) Achieve contact with the person (achieving a relationship with the person); (B) Boiling down the problem to its essential (focusing the problem on its part); (C) Cope actively with the problem (overcome the problem actively).Â AbstrakKekerasan sering dialami oleh remaja, baik dalam bentuk fisik di mana remaja mengalami perlakuan kasar, atau dalam bentuk kekerasan verbal dan psikologis, di mana remaja sering dimarahi dengan kata-kata makian dan hinaan. Kekerasan psikologis yang dialami remaja adalah seringnya mendapatkan ancaman, selalu diatur dan diperintah oleh pelaku. Selain itu, remaja juga mengalami kekerasan dalam bentuk kekerasan finansial, di mana remaja mendapatkan pembatasan dan pengontrolan dalam hal keuangan dengan tidak yang semestinya. Konseling krisis merupakan salah satu cara dalam mengatasi kekerasan dalam keluarga yang dialami oleh remaja. Metode Intervensi krisis merupakan sebuah metode untuk menolong individu mengatasi respons emosionalnya yang negatif dan yang merusak karena peristiwa yang menimbulkan krisis. Salah satu implementasi metode intervensi krisis adalah metode ABC; (A) Achieve contact with person (mencapai hubungan dengan pribadi); (B) Boiling down the problem to its essential (memfokuskan masalah pada bagiannya); (C) Cope actively with the problem (menanggulangi masalah secara aktif).